Snow identification from unattended automatic weather stations images using DANet - Gong, Jie; Wang, Yonghua; Liu, Min; Deng, Fan (Frontiers in Earth Science, 2023)
Identifying snow phenomena in images from automatic weather station(AWS) is crucial for live weather monitoring. In this paper, we propose a convolutional neural network (CNN) based model for snow identification using images from AWS cameras. The model combines the attention mechanism of the DANet model with the classical residual network ResNet-34 to better extract the features of snow cover in camera images. To improve the generalizability of the model, we also use images from public datasets in addition to images taken by cameras from unmanned weather stations.Our results show that the proposed model achieved a POD of 91.65%, a FAR of 7.34% and a TS score of 85.45%, demonstrating its effectiveness in snow identification. This study has the potential to facilitate more efficient and effective weather monitoring in a variety of locations.